Gap and Angulation Change in Total Knee Arthroplasty after Tibia Component Undersizing and Lateralization in Flexion Gap and Extension Gap in Cruciate Retaining Total Knee Arthroplasty Using Computer-Assisted Surgery : Cadaveric Study - Hongku, Natthapong; Chaiyakrit, Pruk; Senwiruch, Chaipipath (Vajira Medical Journal : Journal of Urban Medicine, 2021)
Objective: To demonstrate the varus correction angle after performing the medial tibial reduction osteotomy and tibia component undersizing and lateralization techniques for correcting varus deformity in computer-assisted and cruciate-retaining total knee arthroplasty. Methods: Cadaveric study included 5 bodies (10 knee joints) using total knee arthroplasty surgery assessing the varus correction angle, degree, medial and lateral gap measurement of knee joint during the different angles. Then, medial tibial reduction osteotomy and tibia component undersizing and lateralization were performed by 3 and 6 mm and all parameters were measured. Results: The varus correction angles after 3 and 6 mm medial tibial reduction osteotomy were 2.00 and 2.93 degrees respectively. The medial gap increased 1.5 mm after 3 mm medial tibial reduction osteotomy tibia component undersizing and lateralization in full extension knee position. Conclusions: Medial tibial reduction osteotomy and tibia component undersizing and lateralization were used to correct the varus deformity in total knee arthroplasty. The average of the varus correction angle was only 0.6 degrees per 1 mm of bone cut, therefore, this technique should not recommend to be used alone for severe varus deformity knee.